2021
DOI: 10.1021/acsaelm.0c00913
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Pulse Laser Lift-Off Processing of InGaN/GaN Light-Emitting Diode Chips

Abstract: Gallium nitride (GaN) film delamination is an important process during the fabrication of GaN light-emitting diodes (LEDs) and laser diodes. Here, we utilize 520 nm femtosecond laser pulses, exploiting nonlinear absorption rather than single-photon absorption such as in conventional laser lift-off (LLO) employing excimer or Q-switched laser sources. The focus of this study is to investigate the influence of laser scanning speed and integrated fluence corresponding to laser energy per area during the LLO proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 68 publications
(133 reference statements)
0
34
0
Order By: Relevance
“…reported that the scheme of multi‐photons absorption to induce GaN layer separation based on nonlinear effects normally required a much higher laser fluence than conventional approaches, and it increased the energy consumption and the production cost in the actual production of GaN‐based devices. [ 28 ] More importantly, they found that the nonlinear absorption process resulted in deeper laser penetration depths, which led to the uncontrollability of the delamination region and increased the risk of functional layer damage. Additionally, the surface root mean square (r.m.s.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that the scheme of multi‐photons absorption to induce GaN layer separation based on nonlinear effects normally required a much higher laser fluence than conventional approaches, and it increased the energy consumption and the production cost in the actual production of GaN‐based devices. [ 28 ] More importantly, they found that the nonlinear absorption process resulted in deeper laser penetration depths, which led to the uncontrollability of the delamination region and increased the risk of functional layer damage. Additionally, the surface root mean square (r.m.s.)…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the surface root mean square (r.m.s.) roughness of the separated GaN layer with this scheme was also unsatisfactory (≈68 nm) [ 25,26,28,29 ] and even inferior to that of the GaN surface separated by conventional approaches (≈50 nm). [ 30–32 ] It means the using of multi‐photons absorption in LLO was unfavorable for bonding prefabricated GaN‐based devices to foreign substrates or electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The femtosecond laser (343 nm, 200 kHz, 280 fs (Light Conversion Pharos, Vilnius, Lithuania)) is tightly focused through a high numerical aperture objective lens (NA = 0.95, 40×) and matched with a three-dimensional piezoelectric platform (the strokes of the xand y-axes are 1.5 mm, that of the z-axis is 100 µm, and accuracy is 1 nm) to realize the preparation of micro/nanostructures on the silicon surface [24][25][26][27][28][29]. In addition, the femtosecond laser can also be used to process other materials via multi-photon absorption, for example, lift off GaN [30,31]. After femtosecond laser treatment, a laser-modified region was formed on the silicon surface, changing its physical and chemical properties.…”
Section: Methodsmentioning
confidence: 99%
“…29,30 Similar to the underlying mechanism for femtosecond laser li-off of semitransparent semiconductor materials (e.g., InGaN/GaN LEDs), the use of laser enables the processing of transparent polymers via nonlinear optical interaction, which prevents heating effect surrounding the microholes during the laser ablation process. [31][32][33] The ultra-fast laser system based on an Yb-based commercial femtosecond laser source (SPIRIT-1040, Newport Spectra-Physics GmbH, Germany) was used in this study. This laser has constant parameters, i.e., a center wavelength of 520 nm, a pulse width of 350 fs, and a repetition rate of 200 kHz.…”
Section: Sample Fabrication and Characterizationmentioning
confidence: 99%